Supermolecular structure and selected properties of PA 6/LCO modified fibres - Bączek, M.; Janicki, J. (Polimery, 2011)
The objective of the research presented in this paper was to analyze the influence of the LCO Liquid Crystalline Oligoester (LCO) on the supermolecular structure, thermal and mechanical properties of new fibres prepared from PA 6 and LCO blends. Small angle X-ray scattering (SAXS) and wide angle X-ray diffraction (WAXS) methods were used to determine the structure of LCO modifier and the crystal and lamellar structure of PA 6 matrix of the fibres. Based on DSC measurements thermal properties of these fibres were analyzed. Some results of mechanical tests were also presented. All results of investigations into supermolecular structure, thermal and mechanical properties of PA 6/LCO fibres were compared with the results obtained for unmodified PA 6 fibres.